Initial development of Euterpe oleracea Mart. in function containers used in the production of seedlings - Ramos Filho, Fabiano Luis de Sousa; Bandeira Neto, Nazaro Cavalcante; Pantoja, Cezar Dias; Nascimento, Walnice Maria Oliveira do; Souza, Olavo Tavares de (Revista de Ciências Agroveterinárias, 2023)
The açaizeiro (Euterpe oleracea Mart.) is a natural species of the lowland areas of the Amazon region, with the state of Pará as the largest center of natural dispersion of this palm. Much of its production comes from extractivism and has the potential to increase fruit production by projecting the scenario for the advancement of the species' cultivation to the mainland, but it needs to be framed in market standards, therefore, improvement must occur. of seedling production techniques. Thus, this work aimed to evaluate the initial development in açaí plants, produced in containers with different volumes and substrates, during 360 days in the field. The test was carried out in the experimental field of Embrapa Amazônia Oriental, in Belém, PA. Açaizeiro seedlings of the cultivar BRS Pará, produced in two types of substrates (commercial and conventional) were used. For the production of seedlings, the following types of containers were used: plastic bag with dimensions of 18 x 24 cm (1900 cm³), which is recommended for the production of açaí seedlings and other fruit trees and tubes with volumes of 280, 175 and 95 cm³. The experiment was installed in a completely randomized block design, using four replications and five plants per plot. Field evaluations took place every 60 days after planting. The variables measured were: plant height, stem diameter and number of leaves. It was observed that the treatments in polyethylene bag had greater development in the analyzed variables, regardless of the substrate used. It was found that there was no significant difference between treatments resulting from seedlings produced in tubes. Therefore, it is concluded that the plants of E. oleracea Mart, cultivar BRS Pará, presented greater initial development when coming from seedlings produced in polyethylene bags in relation to the other containers.